Relações entre pensamentos metaparentais, a qualidade da relação coparental, Burnout Parental e a funcionalidade familiar - Oliveira, Danilo Ciconi de (2022)
Metaparenting thoughts (metacognitive thoughts about parenting) indicate parents’ abilities to reflect on and identify strategies that promote their children’s development, but we need to better understand the relationship between these thoughts and the quality of family relationships. Among the various techniques used for observing metacognitive thoughts (including counterfactual and pre-factual thoughts), the presentation of fictional scenarios is a procedure that enables people to reflect and comment on interpersonal interactions. However, the analysis of parents’ metacognitive thoughts about real situations involving their children was expected to be even more useful for understanding the effects of metaparenting thoughts on the quality of family relationships. Thus, the objectives of this study were to: (a) compare metacognitive thoughts for fictitious and real parenting situations, (b) verify associations between metacognitive thoughts and the quality of the coparenting relationship, symptoms of parental burnout, and family functioning, and (c) verify the associations among these three measures of family relationships. This study had a descriptive, comparative and relational design. Participants were 30 mothers (average age of 40.5 years, SD = 5.20 years) with children between the ages of 10 to 14. The participants were recruited using social media networks and data were collected online. They completed a sociodemographic questionnaire, a metaparenting interview (which included questions about fictitious scenarios and a real parenting situation), the Coparenting Relationship Scale, the Brazilian Parental Burnout Assessment, and the APGAR index. Answers to the interview questions were categorized according to the type metacognitive thought for the fictitious and real situations, and then comparisons were made using the Wilcoxon test, and associations were tested using Spearman’s correlation. The number of counterfactual thoughts was similar for fictitious and real situations, but the number of pre-factual thoughts was greater for fictitious than for real situations (Z = 246,5, p < 0,001). There were few significant correlations among metacognitive thoughts and the relationship measures, but many significant relationships among the relationship measures. The sample was small and fathers were not included, but it seems that there must be other factors that modulate the relationship between metaparenting thoughts and the quality of family relationships. In future studies, in addition to evaluating metaparenting thoughts, the ways that these thoughts are discussed and reformulated using socioemotional and interpersonal skills could be examined, to analyze the effects of this broader set of cognitive and socioemotional skills on family relationships.